Mental illness and Health-Seeking Behavior: a systematic review of traditional healing practices in India - Subudhi, Chittaranjan (Journal of spirituality in mental health, 2025)
Mental illness has been widely debated among researchers and health practitioners, leaving many questions about its nature and the experience of those affected. It generally encompasses health conditions characterized by shifts in thought, emotion, behavior, or a combination thereof, often impairing daily functioning. While mainstream views focus on biological abnormalities as key drivers, non-biological perspectives also provide valuable insights. This review seeks to explore the factors that influence health-seeking behavior among individuals with mental illness, specifically examining why people in India often choose to consult traditional healers.